(untitled) - Organisation for economic Co-operation and development (Paris, 1968)
These food import wold not be distubring if there was not a pronounced shortage of foreing exchange in most developing countries, but fod obvious reasons these countries need large and rising imports, especially of investment goods.
Keywords: Cung cấp thực phẩm,Food supply; Các nước đang phát triển,Developing countries